IS THERE A THEORY BASIS FOR AUDIT PROCEDURE? - Kirkham, E. J.; Gaa, C. J. (The Accounting Review, 1939)
Abstract Although auditing, in varying forms, has been practiced for a long time, little attempt has been made to formulate a theory regarding the subject. Accounting is a process of keeping records of current business facts according to a system of theory and practice suitable to the circumstances. The auditor is a critic and auditing is an analytic, retrospective process of examining the system of accounting theory and practice of a specific enterprise. Although many audits fall into the same general class as to purpose, in no two cases are all the conditions identical. Every audit is an individual problem the solution of which requires a thorough understanding of the particular circumstances obtaining in that case. Since the auditor must judge the validity of the evidence supporting the transaction it is necessary for him to be able to recognize what is valid and what is not valid. Verification by impartial testimony based on information in the possession of persons outside the business is the most valid evidence that can be obtained to support any given item or transaction. An auditor must decide whether to secure confirmations from all or only a portion of the customers. In addition he must decide whether to ask each customer circularized for a statement as to the correctness of the balance shown owing to the company or to notify the debtor that he stands charged with the amount, with the request that he advise the auditor as to any exceptions that he may take.